6. FENOMENA PEMILIHAN KEPALA DAERAH DAN PERMASALAHANNYA - Yuniningsih, Tri (FORUM, 2014)
The elections are part of the implementation of political decentralization, by giving full freedom to the people in selecting the candidates for the head area, in accordance with the wishes and preferences of each election, as well as based on the spirit of egalitarianism and voluntarism. Supposedly with the direct election of regional leaders who gave birth to the pure expectations these people, can answer the fundamental problems will handcuff local community. Here's a bit of problems encountered in transmitting the values of democracy at the local level. because democracy is not just a procedural but include process and content.